2007
DOI: 10.1190/1.2734365
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse ERT monitoring of an injection/withdrawal experiment in a shallow unconfined aquifer

Abstract: To quantify performance of 3D time-lapse electrical resistivity tomography (ERT), a sequential injection/withdrawal experiment was designed for monitoring the pump-and-capture remediation of a conductive solute in an unconfined alluvial aquifer. Prior information is incorporated into the inversion procedure via regularization with respect to a reference model according to three protocols: (1) independent regularization involving a single reference model, (2) background regularization involving a reference mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 26 publications
3
64
0
Order By: Relevance
“…Image analysis, from spatially distributed resistances at specific time intervals, is through timelapse electrical-resistivity tomography (TLERT). TLERT's various applications have attracted many researchers: Barker and Moore (1998) for physical-model tests of groundwater flow and contamination; Kemna et al (2002), Cassiani et al (2006), and Oldenborger et al (2007) for tracertest study of aquifers; Olofsson and Lundmark (2009) for impact monitoring of roadside-soil de-icing-salt in saltwater investigation; and Ogilvy et al (2009) for study of near-coast saltwater intrusion; in each, TLERT images relate change in salinity to transport of solutes.…”
Section: Introductionmentioning
confidence: 99%
“…Image analysis, from spatially distributed resistances at specific time intervals, is through timelapse electrical-resistivity tomography (TLERT). TLERT's various applications have attracted many researchers: Barker and Moore (1998) for physical-model tests of groundwater flow and contamination; Kemna et al (2002), Cassiani et al (2006), and Oldenborger et al (2007) for tracertest study of aquifers; Olofsson and Lundmark (2009) for impact monitoring of roadside-soil de-icing-salt in saltwater investigation; and Ogilvy et al (2009) for study of near-coast saltwater intrusion; in each, TLERT images relate change in salinity to transport of solutes.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast 3D inversion produces volumetric images, fully reconstructing the 3D nature of the tracer plume, albeit with decreasing resolution at greater distances from the boreholes. This method has been used to monitor tracer tests on timescales of several hours to a few days, typically using fewer than 10 boreholes, each with some 10 -20 electrodes (Daily and Ramirez, 2000;Binley et al, 2002;Singha and Gorelick, 2005;Oldenborger et al, 2007a;Kuras et al, 2009). In many cases, quantitative estimates can be made of seepage velocities (Sandberg et al, 2002), spatial moments (Binley et al, 2002;Singha and Gorelick, 2005;Looms et al, 2008), hydraulic conductivity (Binley et al, 2002), and tracer mass and concentration (Singha and Gorelick, 2006;Oldenborger et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Acceptable convergence was achieved after 5 iterations. From the time-lapse analysis perspective, the software package allows a joint inversion technique, where the inversion of the first measured resistivity data is used as a reference model to constrain the datasets collected at a later stage, this method has been used in previous research (Loke, 2001;Miller et al, 2008;Oldenborger et al, 2007). Miller et al (2008) compared three methods for time-lapse data inversion and found that using a reference model for the inversion of additional datasets minimised the occurrence of noiserelated time-lapse artefacts.…”
Section: Methodsmentioning
confidence: 99%
“…This technique can be carried out through short time periods (several days with readings taken every few hours) to evaluate the migration of contamination plumes (Radulescu et al, 2007), detection and monitoring of concentration of a conductive contaminant within aquifers (Cassiani et al, 2006;Chambers et al, 2004;Oldenborger et al, 2007), quantification of superficial water infiltration rates into the subsurface (Barker and Moore, 1998) and tracer test monitoring (Monego et al, 2010;Ward et al, 2010). Long term time-lapse resistivity surveys have been applied to monitor seasonal variations on seepage rates (Johansson and Dahlin, 1996;Sjödahl et al, 2008), monitoring salinity within aquifers in coastal areas (de Franco et al, 2009;Leroux and Dahlin, 2006;Ogilvy et al, 2009), safety assessment for storage of nuclear waste (Yaramanci, 2000), estimation of subsurface temperature variation (Morard et al, 2008), observing changes in liquid water saturation and temperature in frozen ground (Hauck, 2002) and monitoring permafrost active layer thickness variation (Kneisel, 2006).…”
Section: Introductionmentioning
confidence: 99%